Multiple distinct forms of CD8+ T cell cross-reactivity and specificities revealed after 2009 H1N1 influenza A virus infection in mice. - Hailong Guo; David J Topham (PLoS ONE)
Influenza primed mice are protected against lethal infection with H1N1 A/CA/04/E3/09 virus, and T depletion and serum transfer studies suggest a T-dependent mechanism. We therefore set out to investigate the quality of the cross-reactive T cell response to CA/E3/09 in mice primed with H3N2 influenza A/Hong Kong/X31 virus. Sequences of the immunodominant nucleoprotein (NP) NP366-374 and acid polymerase (PA) PA224-233 CD8 epitopes from X31 each differ from the CA/E3/09 virus by one amino acid: an M371V substitution at position 6 of the NP peptide, and an S224P substitution at position 1 of the PA peptide, raising questions about the role of these epitopes in protection. PA224-233 peptides from either virus could elicit IFN-γ spot forming cells from mice infected with X31, indicating cross-reactivity of these two peptides. However, no T cell responses to either PA224-233 peptide were detectable after primary CA/E3/09 infection, suggesting it is cryptic in this virus. In contrast, primary responses to the NP366 peptides were detectable after infection with either virus, but did not cross-react in vitro. Similarly, H2-D(b) tetramers of each NP epitope stained CD8+ T cells from each respective virus infection, but did not obviously cross-react. Early after lethal CA/E3/09 challenge, X31 primed mice had enhanced IFN-γ responses toward both NP366 peptides, as well as recall responses to a set of subdominant NP and PA peptides not detectable after primary X31 infection alone. Furthermore, dual-tetramer staining revealed an expanded population of CD8 T cells reactive to both NP366 variant peptides also not seen after the priming infection alone. These observations demonstrate unusual CD8+ T cell cross-reactivity and specificity are elicited after primary and secondary CA/E3/09 influenza virus infections.